2023
DOI: 10.1620/tjem.2022.j114
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors with 30-Day Readmission and the Impact of Length of Hospital Stay on It in Patients with Heart Failure: A Retrospective Observational Study Using a Japanese National Database

Abstract: Heart failure is a major disease, and its 30-day readmission, readmission within 30-day after discharge, negatively impacts patients and society. Thus, we need to stratify the risk and prevent readmission. We aimed to investigate risk factors associated with 30day readmission and examine the impact of length of hospital stay (LOS) on 30-day readmission. Using the Diagnosis-Procedure-Combination database from April 2018 to March 2021, we conducted multiple logistic regression to investigate risk factors with 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…First, we identified the following risk factors for readmission: older age, female, longer LOS, artificial ventilator, tolvaptan, top 50% dosage of loop diuretics, bottom 50% dosage of class III antiarrhythmic agents, hypertension, atrial fibrillation, dilated cardiomyopathy, valvular disease, myocardial infarction, diabetes, and renal disease. Most of these results were consistent with earlier studies 20–27 . We identified that female is a risk factor for readmission.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, we identified the following risk factors for readmission: older age, female, longer LOS, artificial ventilator, tolvaptan, top 50% dosage of loop diuretics, bottom 50% dosage of class III antiarrhythmic agents, hypertension, atrial fibrillation, dilated cardiomyopathy, valvular disease, myocardial infarction, diabetes, and renal disease. Most of these results were consistent with earlier studies 20–27 . We identified that female is a risk factor for readmission.…”
Section: Discussionsupporting
confidence: 92%
“…Most of these results were consistent with earlier studies. [20][21][22][23][24][25][26][27] We identified that female is a risk factor for readmission. Studies on sex differences in patients with heart failure have been conducted, but their results may not be consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of potential readmission risk factors may allow to optimize outpatient management to prevent them: older age, home medical care, tolvaptan usage, dosage of loop diuretics, diabetes, and renal disease were all associated with more frequent outpatient visits. 14 Peak oxygen consumption (VO 2 ) values measurement obtained by the cardiopulmonary exercise testing is recommended to prioritize patients in the transplant recipient list: Its measurement outperformed Heart Failure Survival Score in predicting 1-year and 2-year major outcomes, with the cut-off value of 10.2 (11.8-7.0) mL/kg min for predicting a 20% risk of a major outcome within 2 years. 15 In patients with coronary artery disease, admission levels of growth differentiation factor 15 (GDF-15) were associated with an increased 1-year risk of cardiovascular death, HF, and bleeding outcomes, but not with thrombotic events.…”
Section: Risk Prediction In Heart Failurementioning
confidence: 99%